A "gestalt" framework of emotions and organizing: integrating innate, constructed, and discursive ontologies. Issue 5 (November 2021) - Town, Sophia; Donovan, Matthew C. J.; Beach, Emily
An ongoing debate exists regarding the ontology of emotions; that is, whether emotions are innate biological artifacts, social/discursive constructions, or—although less common in emotion research—both. Growing neuroscientific research provides strong evidence for the third perspective. Yet, this work foregrounds the individual's experience, overlooking the role and context of organizing. In this article, we developed a new perspective of emotions and organizing. Our "gestalt" framework unites innate, socially constructed, and discursive ontologies to explain how emotions exist as innate yet latent organizational potentialities, become salient through social interaction, and are embedded in organizations through discourse. Together, these aspects comprise the gestalt emotion experience—where the whole is something more than its parts. The gestalt view offers organizational actors and scholars practical wisdom for navigating and analyzing emotions in organizations.